Pengaruh Partisipasi Anggaran dan Akuntansi Pertanggungjawaban Terhadap Kinerja Manajerial - Fransiska Simanullang; Sairun Simanullang (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Decentralization of local government management and public demand for transparency and accountability, forcing both central and local governments to create a more transparent and accountable financial management system, the system is expected to realize the financial management in an orderly, economical, effective, and efficient and beneficial to the community . Based on the description of the background, the authors formulate the problem as follows: Does budget participation significantly influence the managerial performance in PT POS Indonesia. Is accountability accounting significantly affect managerial performance in PT POS Indonesia. Is budgetary participation and accountancy accountability affect jointly to managerial performance. To achieve the research objectives in accordance with the expected in preparing this thesis and to obtain conclusions, the data collected will be analyzed with quantitative analysis. Quantitative method is the science or art related to the method (method) of data collection. The data used in this study is not necessarily the whole of a population, because the number of population size of this study is not identified, then to determine the number of samples of the study can use Slovin formula, which is 100 respondents. Based on F test it can be seen that the Budget Participation and Accounting Accountability influence simultaneously, from the test results coefficient determination known that the independent variables (Budget Participation and Accounting Accountability) have contributed to the dependent variable (Managerial Performance) and the rest influenced by other variables outside the independent variable Which has been studied. From the results of Test t (Partial) note that the independent variables (Budget Participation and Accounting Accountability) have a significant influence on Managerial Performance at Post Office Indonesia Branch. From the results of Partial Test (Test T) is known from the Budget Participation and Accounting the most dominant of Managerial Performance is Budgetary participation variable (X1).